Exploring key elements for e-trasformation in commercial banks in Kenya - Maina, Juliet Wangui (My University, 2016)
Digital transformation on a national level is a framework that has been applied to a number of different contexts. Studies in both developed and developing countries have exhibited digital transformation in a manner that reflects its applicability across contexts and scenarios. However, this research explored what happens when the same is applied to organizational contexts in a developing country. The research did not divert too far from the national application of a digital transformation framework, but merely sought to incorporate the organizational perspective, and the different considerations that arise in commercial banks in Kenya; an area which was previously under-explored. A conceptual framework was developed to study only particular elements of digital transformation from qualitative analysis and different sources of data. The findings of this study illustrated that there is a huge uptake of technologies in these commercial banks, but also notes a significant number of limitations that currently exist. The report concludes with proposals as to how these limitations can be addressed through various recommendations, and also considers other avenues for improvement, and future research that can later be applied other contexts.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Arts (in the field of ICT Policy and Regulation). 9th August 2016.
Keywords: Banks and banking--Kenya; Electronic commerce